Fahrenheit 451 [compact disc, unabridged] - Bradbury, Ray. 1920-2012 (Caedmon/Harper Audio, 2001)
In a future totalitarian state where books are banned and destroyed by the government, Guy Montag, a fireman in charge of burning books, meets a revolutionary schoolteacher who dares to read and a girl who tells him of a past when people did not live in fear.